Indelible Deference - R. Todd Gabbard (Oz, 2008)
Steven Holl's addition to the Nelson-Atkins Museum of Art in Kansas City, unveiled to the public on June 9, 2007, was immediately celebrated as one of the most engaging, captivating, and poetic projects in recent years, receiving no less than six prestigious awards in the year since it opened, including the AIA Institute Honor Award.